Al-Kindy College Medical Journal: Time to Move Forward - Al-Mendalawi, Mahmood D. (AL-Kindy College Medical Journal, 2021)
It is well- known that the distinguished scholastic journal is a crucial cornerstone, which contributes to the scientific integrity of a particular academic institution. The establishment of the Al-Kindy College of Medicine (AKCM), University of Baghdad, in 1998 urged the need to issue Al-Kindy College Medical Journal (KCMJ).